IMMU-02. GENOMIC AND TRANSCRIPTOMIC CORRELATES OF IMMUNOTHERAPY RESPONSE WITHIN THE TUMOR MICROENVIRONMENT OF LEPTOMENINGEAL METASTASES. (12th November 2021) - Alvarez-Breckenridge, Christopher; Prakadan, Sanjay; Markson, Samuel; Kim, Albert; Nayyar, Naema; Kuter, Benjamin; Mora, Joana; Shaw, Brian; Lee, Eudocia Quant; Chukwueke, Ugonma; Cahill, Daniel; Sullivan, Ryan; et al.
Abstract: Leptomeningeal disease (LMD) is a devastating complication of solid tumor malignancies, with dire prognosis and no effective systemic treatment options. Over the past decade, the incidence of LMD has steadily increased due to therapeutics that have extended the survival of cancer patients, highlighting the need for new interventions. To examine the efficacy of immune checkpoint inhibitors (ICI) in patients with LMD, we completed two phase II clinical trials utilizing either Pembrolizumab alone or the combination of Ipilimumab and Nivolumab. We investigated the cellular and molecular features underpinning observed patient trajectories in these trials by applying single-cell RNA and cell-free DNA profiling to longitudinal cerebrospinal fluid (CSF) draws from enrolled patients. We isolated and sequenced 34, 742 cells from both the malignant and immune compartment within CSF. Amongst the 19 patients included in the cohort, there were 13 pre-treatment and 24 post-treatment samples, and 9 patients were sampled across multiple timepoints. We detected dynamic changes in immune cell recruitment into the CSF and activation within 30 days of ICI, including increased effector T cell activation and IFN-gamma response pathways within T cells. Moreover, the overall level of IFN-gamma response and antigen processing within 30 days of ICI in malignant cells correlated with survival past clinical trial primary endpoint. Lastly, we observed evidence of longitudinal outgrowth of distinct immunogenic clones over the course of ICI. Overall, our study describes the liquid LMD tumor microenvironment prior to and following ICI treatment and provides unique insights into the compartmental and temporal variation during the course of ICI. Moreover, our findings demonstrate the clinical utility of cell- free and single-cell genomic measurements for LMD research.